2014
DOI: 10.1111/jgs.12648
|View full text |Cite
|
Sign up to set email alerts
|

Quick and Easy Is Not without Cost: Implications of Poorly Performing Nutrition Screening Tools in Hip Fracture

Abstract: Poor screening tool sensitivity leads to undiagnosed malnutrition; tools that are quick and easy to apply are not without cost. Routine nutrition assessment should replace nutrition risk screening in hip fracture settings with a high prevalence of malnutrition reliant on case-mix funding. Further pragmatic studies are urgently required to determine whether findings apply to other elderly inpatient populations with endemic malnutrition, comorbidities, and cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 36 publications
1
47
0
2
Order By: Relevance
“…The lack of a proper screening tool was even considered as one of the reasons for not initiating nutritional support [8,10]. Bell et al evaluated the performance of several nutrition screening tools in hip fracture elderly patients including the MNA-SF and the MUST and found that none of the tools tested met the a priori requirement for sensitivity and specificity [24]. They concluded that since nutritional screening tools, though quick and easy to apply overlooked many malnourished patients and should be replaced by routine nutrition assessments.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a proper screening tool was even considered as one of the reasons for not initiating nutritional support [8,10]. Bell et al evaluated the performance of several nutrition screening tools in hip fracture elderly patients including the MNA-SF and the MUST and found that none of the tools tested met the a priori requirement for sensitivity and specificity [24]. They concluded that since nutritional screening tools, though quick and easy to apply overlooked many malnourished patients and should be replaced by routine nutrition assessments.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The ICD-10-AM classification involves an evaluation of body mass index (BMI; calculated as kg/m 2 ) to detect chronic malnutrition (BMI <18.5) or weight loss with suboptimal dietary intake resulting in fat and/or muscle wasting to detect acute malnutrition. Failure to identify patients at risk of malnutrition in the health care setting can negatively impact funding 21 ; therefore, the nutrition screening and assessment method used must be in agreement with the ICD-10-AM criteria to ensure resources are available for treatment.…”
Section: Figurementioning
confidence: 99%
“…188 Malnutrition was found in 48% of patients with hip fracture in a recent study. 189 A serum albumin level less than 3 g/dL has been associated with poor outcomes after hip fracture. 190 Screening for malnutrition has been studied.…”
Section: Stephen L Kates Md and Amy Kates Ms Rn-bcmentioning
confidence: 99%
“…Screening tools while quick and easy do not perform as well as a complete nutritional assessment in correctly diagnosing malnutrition. 189 Routine nutritional assessment should be standard in management of older patients with fragility fracture. 189,191 Generally, patients with fragility fracture should be fed orally.…”
Section: Stephen L Kates Md and Amy Kates Ms Rn-bcmentioning
confidence: 99%
See 1 more Smart Citation